Сравнительный анализ спектра кристаллических белков и плазмид ряда новых штаммов Bacillus thuringiensis - Исакова, И.А.; Рымарь, С.Е.; Кузнецова, Л.Н.; Кордюм, В.А. (Биополимеры и клетка, 1999)
Изучены основные характеристики ряда новых штаммов В. thuringiensis, выделенных на территории Украины и проявляющих токсичность по отношению к Lepidoptera и Coleoptera (личинкам колорадского жука). Определен их плазмидный составу а также молекулярные массы кристаллических инсектицидных белков, продуцируемых этими штаммами во время спекуляции. Вивчено основні характеристики ряду нових штамів В. thuringieasis, виділених на території України, які проявляють токсичність по відношенню до Lepidoptera та Coleoptera (личинкам колорадського жука). Визначено їхній плазмідний склад, а також мопекулярні маси кристалічних інсектицидних білків, що продукуються цими штамами під час споруляції The spectrum of insecticidal crystal proteins produced by 9 new B. thuringiensis strains isolated in Ukraine was studied. These strains demonstrated high toxicity to Lepidoptera and lower toxicity to Coleoptera (Colorado potato beettle larvae) in biological tests. It was shown that 5 strains produce high molecular weight proteins (137–164 kD), 3 strains produce 76.5 kD proteins, and one produce two proteins (96.5 kD and 77 kD). All the studied strains contain the spectrum of plasmids of both low molecular weight (less than 10 MD) and high molecular weight (more than 30 MD). The strains producing crystal proteins of similar molecular weight differ by plasmid composition.